Reliability and validity of the european portuguese version of the social touch questionnaire - Vieira, Ana Isabel (2022)
Social touch is essential for physical and emotional well-being. However, different meanings can be attributed to physical contact during social interactions and may generate bonding or avoidant behaviors. This personal and unique experience is not usually taken into account in health and social care services. The aim of this study is to produce a valid and reliable European Portuguese version of the Social Touch Questionnaire (STQ, Wilhelm et al. in Biol Psychol 58:181–202, 2001. doi:10.1016/S0301-0511(01)00113-2). The STQ is a self-report questionnaire for adolescents and adults measuring behaviors and attitudes towards social touch. The original version was translated into European Portuguese using a forward-back translation process and its feasibility was examined. To evaluate the psychometric properties, a total of 242 Portuguese university students participated in the study (21.3 ± 3.8 years). The STQ was considered feasible, showed adequate internal consistency (Cronbach’s a = .734), and the test–retest correlation with the STQ items demonstrated a high concordance between the tests over a two-week interval (ICC = .990; n = 50). Validity tests were performed, comparing the total score of the STQ with that of the anxiety and avoidance subscales of the Social Interaction and Performance Anxiety and Avoidance Scale (SIPAAS). A very significant conceptual convergence was confirmed between the STQ and with the SIPAAS-Anxiety (r = .64; p\.0001) and with the SIPAAS-Avoidance (r = .59; p\.0001). The exploratory factor analysis, with Promax rotation, revealed 3 factors: dislike of physical touch, liking of familiar physical touch and liking of public physical touch (Cronbach’s alphas ranged from .68 to .75). Psychometric properties confirmed the adaptation of the STQ to the Portuguese culture. It is a reliable and valid self-report questionnaire and it appears to be a useful tool to assess behaviors and attitudes towards social touch.